Educational Technology and Teacher Education: Barriers and Gates in South America - Constantino, Gustavo Daniel (2014)
Historically, Educational Technology (EdTech) and Teacher Education (TE) have shared a conflicted relationship, particularly where practicing teachers have not been trained in ET in a manner so that they are able to coherently and efficiently incorporate the new educational technology into their classrooms and schools. In Latin America’s diverse scenario, our analysis is focused on a scenario consisting of Argentina and Uruguay. In this scenario, we identify the social and cultural context where teacher education and teaching practice take place, the EdTech-related programs with the greatest impact, and the “barriers” hindering access to and the application of EdTech, as well as the “bridges” or “gates” that facilitate their effective incorporation to teaching and learning both at schools and in teacher education. Lastly, we propose some courses of action to reduce these barriers and widen the gates connecting EdTech and school settings.